2020
DOI: 10.3389/fneur.2019.01380
|View full text |Cite
|
Sign up to set email alerts
|

Central Neuropathic Pain and Profiles of Quantitative Electroencephalography in Multiple Sclerosis Patients

Abstract: Pain has a significant impact on the quality of life of patients with multiple sclerosis (MS). However, the neurophysiological mechanisms of central neuropathic pain in a MS course are not known. We hypothesized that changes in power spectral density (PSD) that take place in the electroencephalography (EEG) of MS patients with and without the central neuropathic pain (CNP) would differ. The study aimed to assess the features of quantitative EEG using the PSD indicator along with peak frequencies in the standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…2018 ). Other studies also indicate a strong association between downregulation of I h or HCN channel deletion in the cortex and increased δ and θ frequency oscillations during the wake state and sleep ( Krupina et al. 2020 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…2018 ). Other studies also indicate a strong association between downregulation of I h or HCN channel deletion in the cortex and increased δ and θ frequency oscillations during the wake state and sleep ( Krupina et al. 2020 ).…”
Section: Discussionmentioning
confidence: 97%
“…1999 ), as well as in patients with MS ( Leocani et al. 2000 ; Leocani and Comi 2000 ; Krupina et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…1. Central neuropathic pain [53,43] -these articles dealt with neuropathic pain caused by central nervous system disorders (multiple sclerosis) and spinal cord injuries;…”
Section: Articles On the Study Of Eeg Recordings With Neuropathic Painmentioning
confidence: 99%
“…Cognitive deficits Correlation between increased alpha power (global) and overall deficits as well as attention/IPS and memory deficits [28][29][30] Trend toward a correlation between increased theta power (i.e., parietotemporal regions) and global as well as memory deficits [29] Correlation between increased frontal theta/beta waves ratio and attentional/IPS deficits [28,38] Fatigue Correlation between fatigue and abnormalities involving the cortico-cortical connectivity in beta/theta bands and the sensorimotor network activity of the left dominant hemisphere in the beta band [9][10][11][12] Correlation between fatigue and increased beta temporo-parietal FCR and increased beta and theta fronto-frontal FCR [12] Increased alpha and decreased beta SW in the left hemisphere among fatigued patients; correlation between beta SW and fatigue [12] Increased ERD and ERS in frontocentral regions among fatigued patients [13]; correlation between ERD/ERS and fatigue Correlation between asymmetry of right and left sensorimotor cortices EEG power and fatigue [16] Increased interhemispheric connectivity among fatigued patients; correlation between the interhemispheric coherence index and fatigue during a right-hand movement [16] Pain Slowing of alpha peak power, increase of the alpha power and decrease of the beta-band power in regions belonging to the pain matrix in patients with MS suffering from chronic pain; correlation between such abnormalities and pain intensity [35] Increased absolute and relative PSD in the beta bands as well as absolute PSD in beta and theta bands among patients with MS suffering from central neuropathic pain [37] FCR, Functional connectivity at rest; HC, Healthy controls; EEG, Electroencephalography; ERD, Event-related desynchronization; ERS, Event-related synchronization; IPS, information processing speed; MS, Multiple sclerosis; PSD, Power spectral density; SW, Small-worldness.…”
Section: Symptom Association With Eeg Datamentioning
confidence: 99%
“…Such abnormalities involved the links between the salience network and each of the default mode network, the ascending nociceptive pathway, and the descending anti-nociceptive pathway [34][35][36]. In resting-state MEG or EEG studies, PwMS with chronic pain were found to have a slowing of peak power frequency in the alpha band [35], an increased power in the alpha band, or a decreased power in the beta band in regions that belong to the pain matrices with a correlation with pain intensity [35,37]. Compared to PwMS without central neuropathic pain (CNP), those suffering from CNP had higher absolute and relative power spectral density (PSD) in the beta band and higher absolute PSD in the theta and beta bands in most of the studied areas [37].…”
Section: Introductionmentioning
confidence: 99%